Genetic analysis in traditional rice landraces of southern india for puffing quality (Bangladesh Journal of Botany, 2024)
The present investigation was carried out at Department of Plant Breeding and Genetics, Agricultural College and Research Institute, Tamil Nadu Agricultural University, Madurai during 2021 - 2022. The study comprising of 23 traditional rive varieties or landraces of Southern India were analyzed for 16 quality traits to study the extent of variability and character association. Norungan, Navarai, Chinnar and Thooyamalli are the landraces that had maximum value for amylose content, expansion volume, expansion ratio, bulk density and puffing yield. High PCV and GCV were observed for the traits bulk density, expansion of volume, expansion ratio and puffing yield. High heritability coupled with high genetic advance as per cent of mean recorded for most of the traits except hulling percentage, milling percentage and head rice recovery. This proved that these traits are governed by additive gene effects and the process of selection would be effective to improve these traits. Character association studies revealed that the improvement of the traits viz., kernel length, hulling percentage, fat content, gelatinization temperature, gel consistency and bulk density are the key parameters to avail good puffing quality. Based on the overall performance, the genotypes Norungan, Navarai, Chinnar and Thooyamalli can be selected for future breeding programme to obtain new recombinant types for premium quality puffing.Bangladesh J. Bot. 53(4): 981-990, 2024 (December)